2009
DOI: 10.1621/nrs.07004
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to investigate the subcellular distribution of nuclear receptors in vivo

Abstract: Subcellular compartmentalisation and the intracellular movement of nuclear receptors are major regulatory steps in executing their transcriptional function.Though significant progress has been made in understanding these regulatory processes in cultured mammalian cells, such results have rarely been confirmed within cells of a living mammal. This article describes a simple, time-efficient approach to study the nuclear versus cytoplasmic accumulation of nuclear receptors and the regions of nuclear receptor prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Because several studies suggested that hPXR localization is important for its function [3436], we next examined whether the S350D mutation can alter the subcellular localization of hPXR. HepG2 cells expressing FLAG-tagged wild-type or mutant hPXR were treated with either DMSO or SR for 12 h; the subcellular localization of hPXR was visualized by fluorescence microscopy and quantified by the proportion of cells with nuclear FLAG staining.…”
Section: Resultsmentioning
confidence: 99%
“…Because several studies suggested that hPXR localization is important for its function [3436], we next examined whether the S350D mutation can alter the subcellular localization of hPXR. HepG2 cells expressing FLAG-tagged wild-type or mutant hPXR were treated with either DMSO or SR for 12 h; the subcellular localization of hPXR was visualized by fluorescence microscopy and quantified by the proportion of cells with nuclear FLAG staining.…”
Section: Resultsmentioning
confidence: 99%
“…The first evidence of PXR translocation came from studies in mouse liver, indicating that mouse PXR (mPXR) was predominantly localized in the cytoplasm of hepatocytes prior to activation and accumulated in the nucleus following treatment with PCN [9, 105]. Subsequent analysis in the same study, led to the identification of a typical bipartite NLS located in the DBD (66–92) of mPXR, which differs from the leucine-rich XRS of CAR located near the C-terminal within the LBD (Fig.…”
Section: Pregnane X Receptormentioning
confidence: 99%
“…What differentiates PXR from CAR is that PXR is activated only via direct binding to a selective ligand [Sueyoshi and Negishi, 2001]. Although early studies supported the notion that PXR resides in the nucleus, either in absence or in presence of an inducer [reviewed in Sueyoshi and Negishi, 2001], mouse PXR has later been identified to be localized in the cytoplasm, until activated by a ligand and translocated into nucleus [Kawana et al, 2003;Matic et al, 2009].Indeed, mPXR is sequestered in the cytoplasm in the absence of a ligand, bound to a complex consisting of the receptor, the co-chaperone CCRP (for CAR Cytoplasmic Retention Protein, also designated as DNAJC7) and the heat shock 90 (Hsp90) protein.…”
Section: Cyp3a4mentioning
confidence: 99%